ASPECTS OF INCREASING THE INVESTMENT ACTIVITY OF SMALL INDUSTRIAL ZONES IN UZBEKISTAN (Ustozlar uchun, 2024)
Annotation. The article examines processes related to aspects of increasing the investment activity of small industrial zones in Uzbekistan. Factors influencing the process of ensuring investment activity in small industrial zones are studied theoretically and methodologically.